A Frequency-Based Conceptual Framework for Interpreting Force, Boundary, and Space - Adona, Joel (International Journal of Sustainability and Advanced Integrated Research, 2026)
This paper develops a frequency-based conceptual framework for interpreting selected relationships among force, boundary formation, and space. The original draft proposed the use of temporal frequency and distance frequency to reformulate classical expressions of velocity, force, boundary, and space. To make the framework suitable for journal presentation, the present version organizes the proposal as an exploratory theoretical model rather than as a replacement for established physical laws. The framework defines temporal frequency as f_t = 1/t and distance frequency as f_d = 1/d, allowing velocity to be expressed as v = f_t/f_d. From this basis, the paper distinguishes a mass-frequency interaction index, Φ = m f_t, from a dimensionally compatible force expression, F* = m f_t²/f_d. It also reformulates the proposed boundary equation as a density-related term, D_B = m f_d³, and extends it into a pressure-related proxy when linked with velocity. Finally, the proposed space equation is interpreted as a spatial-energy interaction term, S_E = m v², rather than as literal geometric space. Through dimensional analysis and conceptual comparison with standard mechanics, the paper identifies the possible usefulness, limits, and validation requirements of the proposed framework. The study concludes that frequency-based notation may serve as a heuristic model for organizing relationships among time, distance, mass, and motion, but further mathematical proof, simulation, and experimental testing are necessary before the framework can be treated as a physical theory.